Governing Our Souls, Mutilating Our Bodies – The appropriation of social media as a means of corporeal annihilation, resisting the neoliberal logic of self-optimization - Bächle, Thomas Christian (AoIR Selected Papers of Internet Research, 2013)
The theory of governmentality assumes a logic of self-optimization and self-regulation to be characteristic of neoliberal societies. This research paradigm has been widely used to analyze social and political phenomena, particularly in the fields of bio power and bio politics. It has also been productively applied to cultural phenomena, such as media technologies – digital media technologies in particular – which can be interpreted as instruments of constructing and promoting bio-narratives in accordance with a neoliberal order of optimization. This presentation will address digital phenomena (anorexia, HIV, suicide and the mutilation of bodies in social media) which do not fit this logic of optimization, but on the contrary offer instruments of self-destruction and annihilation. It will hint at the limits of the concept of governmentality and at the same time argue that these phenomena are extraordinary examples of an oppositional appropriation of the internet, resisting the complex power/knowledge exerted on post-modern subjects.